Direct Umbilical Vein Injection of Epinephrine with Cut-Cord Milking in an Ovine Model of Neonatal Resuscitation - Payam Vali; Peggy Chen; Evan Giusto; Amy Lesneski; Morgan E. Hardie; Heather K. Knych; Deepika Sankaran; Ziad Alhassen; Houssam M. Joudi; Satyan Lakshminrusimha (MDPI AG, 2024)
Background: An umbilical venous catheter (UVC) is the preferred route of epinephrine administration during neonatal resuscitation but requires specialized equipment, expertise, and time. Hypothesis: Direct injection of epinephrine into the umbilical vein (UV) followed by milking a ~20 cm segment of cut umbilical cord to flush the epinephrine (DUV + UCM) will lead to a quicker administration and earlier return of spontaneous circulation (ROSC) compared with epinephrine given through a UVC. Design: Eighteen near-term asphyxiated lambs were randomized to receive a low-UVC or DUV + UCM of epinephrine at 0.02 or 0.03 mg/kg doses. Outcome measures: A total of 16/18 lambs achieved ROSC with a similar mean (±SEM) time to ROSC [DUV + UCM vs. low-UVC (4.67 ± 0.67 vs. 3.99 ± 0.58 min); p = 0.46]. Two out of ten lambs in the DUV + UCM group required UVC placement for additional epinephrine. The administration of the first dose of epinephrine was similar (DUV + UCM-2.97 ± 0.48 vs. UVC-4.23 ± 0.58 min; p = 0.12). Both methods yielded similar epinephrine concentrations (peak concentrations of 253 ± 63 and 328 ± 80 ng/mL for DUV + UCM and UVC EPI, respectively). Conclusions: DUV + UCM resulted in a ROSC success of 78% following the first epinephrine dose and showed similar epinephrine concentrations to UVC. Clinical studies evaluating DUV + UCM as an alternate route for epinephrine while intravenous access is being established are warranted.